2022
DOI: 10.1093/brain/awac463
|View full text |Cite
|
Sign up to set email alerts
|

Case-control study developing Scottish Epilepsy Deaths Study Score to predict epilepsy-related death

Abstract: This study aims to develop a risk prediction model for epilepsy-related death in adults. In this age- and sex-matched case-control study, we compared adults (aged ≥16 years) who had epilepsy-related death between 2009–2016 to living adults with epilepsy in Scotland. Cases were identified from validated administrative national datasets linked to mortality records. ICD-10 cause-of-death coding was used to define epilepsy-related death. Controls were recruited from a research database and epilepsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 73 publications
1
19
0
Order By: Relevance
“…A reprise of this study in a Canadian cohort reported a similar incidence in children [9]. Remarkably, several newer studies in a variety of countries and patient populations reveal similar incidences as those reported in the Swedish and Canadian studies [6,10–19].…”
Section: Epidemiology Of Sudden Unexpected Death In Epilepsysupporting
confidence: 78%
See 1 more Smart Citation
“…A reprise of this study in a Canadian cohort reported a similar incidence in children [9]. Remarkably, several newer studies in a variety of countries and patient populations reveal similar incidences as those reported in the Swedish and Canadian studies [6,10–19].…”
Section: Epidemiology Of Sudden Unexpected Death In Epilepsysupporting
confidence: 78%
“…Several risk factors for SUDEP have been identified, including having frequent generalized convulsive seizures (GCS), having nocturnal seizures, being found prone and being male, among others [7]. Importantly, these same themes emerged in most of the studies conducted in other countries and published in the last year or so [6,[10][11][12][13][14][15][16][17][18][19]22]. Many of these risk factors have been combined into a new risk assessment scale, the SUDEP clinical risk score (SUDEP-CARE) [23].…”
Section: Risk Factorsmentioning
confidence: 99%
“…The primary driver of which variables are selected will be consensus amongst the clinical research team and our Public Advisors (people affected by epilepsy) on which predictors are most important clinically and are readily accessible in the datasets (i.e. missing data patterns will be incorporated into the decision-making) [10]. The focus will not be on the strength of the predictor (e.g.…”
Section: Model Development and Validationmentioning
confidence: 99%
“…(i) consider each binary outcome (A = seizure-related ED or hospital admission, and B = epilepsy-related death) separately, and develop individual prediction models for each using logistic regression [2,10];…”
Section: Model Development and Validationmentioning
confidence: 99%
See 1 more Smart Citation